The Method of Authenticating Hadith: A Study of Al-Hakim's Theory and Practice in Al-Mustadrak 'Ala Al-Shahihain" - Itho Athoillah (al-Afkar, Journal For Islamic Studies, 2026)
Al-Hakim was a renowned hadith scholar who had a significant influence in the Islamic intellectual tradition. One of his most well-known works is al-Mustadrak ‘ala al-Shahihain, which reflects his application of methods in assessing the authenticity of hadiths. This study aims to further explore al-Hakim’s methodology in determining the validity of hadiths as demonstrated in his work. Using a descriptive-analytical approach, this research concludes that al-Hakim employed the principle of ijtihad in establishing methods for authenticating hadiths. He categorized these methods into four main perspectives: (1) based on the criteria for hadith authenticity, (2) based on hadith classification, (3) based on the analysis of sanad (chain of transmission) and matan (text), and (4) based on standards for determining hadith authenticity. In assessing the validity of hadiths according to narrators’ criteria, al-Hakim classified them into five categories: (1) hadiths that meet the criteria of Shahihain, (2) hadiths that meet the criteria of al-Bukhari, (3) hadiths that meet the criteria of Muslim, (4) hadiths that meet the criteria of al-Hakim, and (5) hadiths that were not evaluated by al-Hakim.